The Effect of Flipped Classroom on EFL Learners’ Competence with Different Learning Styles: A Meta-Analysis - Lailul Fitriah; Mujiono Mujiono; Riza Weganofa (Journal of English Language Teaching and Linguistics, 2025)
This meta-analysis examines the effectiveness of the Flipped Classroom (FC) model in enhancing EFL learners' competence, focusing on the impact of different learning styles․ This study synthesizes data from 14 quasi-experimental studies published between 2015 and 2024, following PRISMA guidelines․ The study evaluates the overall effect size (ES) and applies moderator analysis to assess variations across student majors, language learning targets, education levels, and geographic regions․ Findings: Results indicate a moderate positive impact of the FC model on EFL learners' competence (ES = 1․99, 95% CI: 0․38 – 3․59)․ Notably, English-major students and those focusing on reading comprehension showed the most significant improvement․ Additionally, learners at the college level benefited more than high school students․ Implications: These findings suggest that the FC model can be effectively tailored to different learning styles, supporting a more personalized and interactive EFL learning experience․ The study underscores the need for further research to optimize FC implementation across diverse educational and cultural contexts․